Blockchain e sua utilidade no comércio internacional - Brunoni, Pedro Henrique (My University, 2024)
Currently, emerging technological innovations in various sectors of society are highly relevant to the business world. With globalization and technological advancement, companies operating in the international market must adopt technological solutions to ensure the competitiveness of their services and products. One such technology is Blockchain, which can be widely applied to solve daily problems and provide significant benefits in the context of international trade. In light of this, the objective of this study was to analyze the current application of Blockchain, with a particular focus on International Trade. The research aims to answer the central question: "How does the use of Blockchain contribute to international trade?" This research was conducted through an exploratory approach, utilizing qualitative data to analyze the application of this technology in foreign trade. The results obtained through the review of articles reveal both the benefits, such as security and process optimization, and the challenges, such as the high initial costs of implementing Blockchain. Moreover, the study highlights challenges related to scalability and integration with traditional financial systems, concluding that, although promising, the technology still requires adaptations to achieve efficient and sustainable implementation in international trade.[resumo fornecido pelo autor]
Atualmente, as inovações tecnológicas emergentes em várias áreas da sociedade são extremamente relevantes para o setor empresarial. Com a globalização e o avanço da tecnologia, as empresas que atuam no mercado internacional precisam adotar soluções tecnológicas para garantir a competitividade de seus serviços e produtos. Uma dessas tecnologias é o Blockchain, que pode ser amplamente aplicada para solucionar problemas diários e proporcionar benefícios significativos no contexto do comércio internacional. Frente a isso, o objetivo deste estudo foi analisar a aplicação atual do Blockchain, com um foco particular no Comércio Internacional. A pesquisa busca responder à questão central: "Como a utilização do Blockchain contribui para o comércio internacional?" Esta pesquisa foi conduzida por meio de uma abordagem exploratória, utilizando dados qualitativos para analisar a aplicação dessa tecnologia no comércio exterior. Os resultados alcançados por meio da leitura de artigos, revelam tanto os benefícios, como a segurança e otimização de processos, quanto as dificuldades, como os altos valores iniciais da implementação do Blockchain. Além disso, o estudo evidencia desafios em relação à escalabilidade e à integração com sistemas financeiros tradicionais, concluindo que, embora promissora, a tecnologia ainda demanda adaptações para alcançar uma implementação eficiente e sustentável no comércio internacional. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Inovações tecnológicas; Blockchains (Base de dados)